2023
DOI: 10.1007/s00442-023-05402-0
|View full text |Cite
|
Sign up to set email alerts
|

May future climate change promote the invasion of the marsh frog? An integrative thermo-physiological study

Abstract: Hilighted student paper Through the study of an overlooked invasive frog species, we show that multi-traits methods improve our understanding of how an invasive ectotherm may benefit from climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 83 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Ecological surveys are starting to demonstrate the negative impact of marsh frogs on native wildlife (especially other amphibians, Denoël et al., 2022; Pille et al., 2021), and this impact may intensify with climate change, given the broad thermal tolerance of some alien lineages (Padilla et al., 2023). Water frogs thus strike as one of the most diverse and successful amphibian invaders worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecological surveys are starting to demonstrate the negative impact of marsh frogs on native wildlife (especially other amphibians, Denoël et al., 2022; Pille et al., 2021), and this impact may intensify with climate change, given the broad thermal tolerance of some alien lineages (Padilla et al., 2023). Water frogs thus strike as one of the most diverse and successful amphibian invaders worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, molecular surveys aimed at tracing emerging biological invasions, notably by the marsh frogs (P. ridibundus complex), following uncontrolled introductions linked in part to the international trade for the frog leg industry (e.g., Bellati et al, 2023;Dufresnes et al, 2018;Dufresnes & Dubey, 2020;Holsbeek et al, 2008). Today, Pelophylax invaders are becoming a strong conservation concern, due to their broad habitat tolerance (Denoël et al, 2022), potential performances under future climate change (Padilla et al, 2023), fierce predation on native batrachofauna (Pille et al, 2021) and invertebrates (Pille et al, 2023), potential vectors of amphibian diseases such as chytridiomycosis (Baláž et al, 2014), and the risk to deregulate autochthonous hybridogenetic systems through hybridization and competition (Holsbeek & Jooris, 2010;Quilodrán et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Larzac, marsh frogs were introduced at least two times, with individuals genetically assigned to populations as far as South-Eastern Europe as including alleles of both the kurtmuelleri and ridibundus lineages (Dufresnes et al, 2017a). These frogs have now colonized most of the southern part of the plateau (Denoël et al, 2022), which may have been facilitated by climate change given their preference for warm temperatures (Padilla, Herrel & Denoël, 2023).…”
Section: Study Sites and Speciesmentioning
confidence: 99%
“…All animals were PIT-tagged during capture in the field allowing individual identification (Biolog ID, 12 mm tag). The temperature during trials was the same as the room temperature, which was set at 24°C, a temperature close to the thermal preference of this population (Padilla et al, 2023). Frogs were kept a week without manipulation to allow them to acclimate to laboratory conditions before the onset of observations.…”
Section: Housingmentioning
confidence: 99%
“…They impact native populations through genetic processes (Holsbeek and Jooris, 2010) as well as predation (Pille et al, 2021;Pille et al, 2023). Previous studies have shown that marsh frogs have a high ecological flexibility (Denoël et al, 2022;Ivanova and Berzin, 2019) and show behavioural and physiological traits that favour their invasion (Padilla et al, 2023). Here we aimed to link variation in physiology and performance to anatomical features to highlight which parts of the body may favour their invasion success.…”
Section: Introductionmentioning
confidence: 98%